Surgical strategy for femoral shaft fractures in severely injured patients: A 13-year experience from a tertiary trauma centre. Issue 4 (April 2021) - Kuhmola, Antti; Simons, Tomi; Handolin, Lauri; Brinck, Tuomas
Highlights: Early definitive care is the prevailing treatment strategy in severely injured femoral shaft fracture patients treated at a tertiary trauma centre. Patients treated with damage control orthopaedics are more severely injured particularly having sustained worse intracranial and thoracic injuries. In addition to injury related factors, treatment strategy decision making was influenced by non-injury related factors in only a minority of cases. Despite improved car safety, motor vehicle accidents remain the principle mode of injury in severely injured patients with femoral shaft fractures. Abstract: Background: The treatment strategy of femoral shaft fractures in polytraumatised patients has evolved over the years and led to improved outcomes for these patients. However, there is still controversy regarding the optimal treatment strategy and surgical care can differ markedly from one country to another. We investigate the surgical treatment strategy (Early Definitive Care (EDC) or Damage Control Orthopaedics (DCO)) implemented in the care of severely injured patients with femoral shaft fractures treated at a single tertiary trauma centre in southern Finland and factors affecting decision making. Methods: The Helsinki Trauma Registry (HTR) was used retrospectively to identify severely injured patients (New Injury Severity Score [NISS] ≥ 16) treated from 2006 through to 2018 with concomitant femoral shaft fractures. Patients <16 years old, with isolated head injuries, dead on arrival and those admitted >24 h following the injury were excluded. Based on their initial surgical management strategy, femoral fracture patients were divided into EDC and DCO groups and compared. Results: Compared to other trauma-registry patients, those with femoral shaft fractures are younger (30.9 ± 15.9 vs. 47.0 ± 19.7, p <0.001) and more often injured in road traffic accidents (64.1% vs. 34.4%, p <0.001). The majority (78%) of included patients underwent EDC. Patients who underwent DCO were significantly more severely injured (NISS: 40.1 ± 11.5 vs. 27.8 ± 10.1, p <0.001) with longer lengths of stay in ICU (15.4 ± 9.8 vs. 7.5 ± 6.1 days, p <0.001) and in hospital (29.9 ± 29.6 vs. 13.7 ± 11.4 days, p <0.001) than patients treated with EDC. Decision making was based primarily on injury related factors, while non-injury related factors may have contributed to choosing a DCO approach in a small number of cases. Conclusion: Early definitive care is the prevailing treatment strategy in severely injured femoral shaft fracture patients treated at a tertiary trauma centre. Patients treated with DCO strategy are more severely injured particularly having sustained worse intracranial and thoracic injuries. In addition to injury related factors, treatment strategy decision making was influenced by non-injury related factors in only a minority of cases.